Фосфорилированный углеродный сорбент для очистки воды от тяжелых металлов - Хохотва, Александр Петрович; Малыхина, Карина Артуровна; Лиштва, Павел Валерьевич; Федорок, Яна Анатолиевна (НТУ "ХПИ", 2017)
Синтезирован фосфорсодержащий углеродный сорбент путем термической обработки (при 170°С) сосновых опилок, предварительно пропитанных растворами (NH₄)₃PО₄ различной концентрации. Исследовано влияние коэффициента пропитки и длительности карбонизации на эффективность извлечения Cu(II) из модельных растворов. По сорбции метиленового синего установлено, что отмывка сорбента после карбонизации кипячением заметно увеличивает удельную сорбционную площадь и способствует росту удельной емкости сорбента по меди. Процесс сорбции Cu(II) лимитируется диффузией металла в микропорах.

Phosphorus-containing carbon sorbent was synthesized by heat treatment at 170 °C of pine sawdust, pre-impregnated with (NH₄)₃PО₄ solutions of various concentrations. The ammonium salt decomposed, releasing phosphoric acid, having dehydrating properties and capable of forming of acidic ethers of lignin and cellulose. This lead to introduction of P-atom into functional groups of the carbon sorbent, that in turn had positive impact on sorption properties of the material to heavy metals. The effect of the impregnation rate and duration of carbonization on the efficiency of Cu(II) extraction from model solutions was studied. The best results were obtained at impregnation rate 0,7-1,0 and carbonization time 1-2 hours. The extension of carbonization time to 5 hours significantly – at more than 3 times – worsened the sorption properties of obtained materials. As found by sorption of methylene blue, boiling of the sorbent after carbonization considerably increased the specific sorption area and contributed to the growth of specific sorbent capacity on copper due to better dissolving and washing out of tar and other products of carbonization of lignocellulosic material from pore volume. Predominant mechanism of copper sorption is chelation and only 8-11% of the metal was removed due to cation exchange. Kinetic studies revealed that concentration of Cu(II) dropped at two times during 30 min of sorption process. The most rapid decrease was observed during first 10 min that corresponded to the metal sorption in meso- and macropores. The process of Cu(II) sorption was limited by diffusion of metal in the micropores. Thus, phosphorus-containing carbon sorbent obtained by heat treatment of pine sawdust, soaked with (NH4)3PO4, is a new material with largely improved sorption properties to heavy metals, compared to traditional carbon sorbents.
Phosphorylated carbon sorbent for the removal of heavy metals from water
Keywords: сосновые опилки; фосфорилирование; фосфат аммония; тяжелые металлы; адсорбция; pine sawdust; phosphorylation; ammonium phosphate; heavy metals; adsorption